Mechanics of materials - Gere, James M.; Goodno, Barry J. (Australia : Cengage Learning Asia Pte Ltd, 2013)
This text develops student understanding along with analytical and problem-solving skills. The main topics include analysis and design of structural members subjected to tension, compression, torsion, bending, and more.
1. Tension, compression and shear -- 2. Axially loaded members -- 3. Torsion -- 4. Shear forces and bending moments -- 5. Stresses in beams (basic topics) -- 6. Stresses in beams (advanced topics) -- 7. Analysis of stress and strain -- 8. Applications of plane stress (pressure vessels, beams and combined loadings) -- 9. Deflections of beams -- 10. Statically indeterminate beams -- 11. Columns -- 12. Review of centroids and moments of inertia -- App. A. Systems of units and conversion factors -- App. B. Problem solving -- App. C. Mathematical formulas -- App. D. Properties of plane areas -- App. E. Properties of structural-steel shapes -- App. F. Properties of structural timber -- App. G. Deflections and slopes of beams -- App. H. Properties of materials.
Includes index.
Keywords: MATERIALS